Association of transient orthostatic hypotension with falls and syncope in patients with Parkinson disease. (24th November 2020) - Fanciulli, Alessandra; Campese, Nicole; Goebel, Georg; Ndayisaba, Jean Pierre; Eschlboeck, Sabine; Kaindlstorfer, Christine; Raccagni, Cecilia; Granata, Roberta; Bonuccelli, Ubaldo; Ceravolo, Roberto; Seppi, Klaus; Poewe, Werner; et al.
Abstract : Objectives: To assess the frequency of transient orthostatic hypotension (tOH) and its clinical impact in Parkinson disease (PD), we retrospectively studied 173 patients with PD and 173 age- and sex-matched controls with orthostatic intolerance, who underwent cardiovascular autonomic function testing under continuous noninvasive blood pressure (BP) monitoring. Methods: We screened for tOH (systolic BP fall ≥20 mm Hg or diastolic ≥10 mm Hg resolving within the first minute upon standing) and classic OH (cOH, sustained systolic BP fall ≥20 mm Hg or diastolic ≥10 mm Hg within 3 minutes upon standing). In patients with PD, we reviewed the medical records of the 6 months preceding and following autonomic testing for history of falls, syncope, and orthostatic intolerance. Results: tOH occurred in 24% of patients with PD and 21% of controls, cOH in 19% of patients with PD and in none of the controls, independently of any clinical–demographic or PD-specific characteristic. Forty percent of patients with PD had a history of falls, in 29% of cases due to syncope. Patients with PD with history of orthostatic intolerance and syncope had a more severe systolic BP fall and lower diastolic BP rise upon standing, most pronounced in the first 30–60 seconds. Conclusions: tOH is an age-dependent phenomenon, which is at least as common as cOH in PD. Transient BP falls when changing to the upright position may be overlooked with bedside BP measurements, but contribute to orthostatic intolerance and syncope in PD. Continuous noninvasive BP monitoring upon standing may help identify a modifiable risk factor for syncope-related falls in parkinsonian patients.